Temporal Depolarization Suppressed POTDR System for Quasi-Distributed Instantaneous Intrusion Sensing and Vibration Frequency Measurement - Chaodong Wang; Yaling Zhou; Hao Wu; Can Zhao; Jianguan Tang; Ciming Zhou; Songnian Fu; Ping Shum; Ming Tang (IEEE Photonics Journal)
Theoretical investigation on the mechanism of temporal depolarization effect in a polarization optical time-domain reflectometry (POTDR) system is conducted. First, the relationship between the dynamic range of the incomplete POTDR system and the degree of polarization (DOP) of the backscattered optical signal is derived. Second, a temporal depolarization suppressed POTDR system is proposed by introducing quasi-distributed Fresnel reflections. Third, the DOP distribution of the proposed system is demonstrated by numerical simulations and experiments. It is shown that the temporal depolarization effect can be significantly suppressed to maintain sufficient dynamic range for fast and accurate polarimetric measurement. The signal-to-noise ratio (SNR) of the received optical signal is also improved with the help of Fresnel reflections. With high DOP and improved SNR, instantaneous intrusion sensing and accurate vibration frequency measurement along the fiber link have been achieved without performing any data averaging.